Breaches of Gender Relations in Agricultural Cooperatives in Camagüey Municipality, Cuba - Maribel Almaguer Rondón; Kirenia Saborit Valdes; Marianela Parrado Álvarez; Yamilka Infante Mesa; Evelyn Márquez Alvarez; Elizabeth Sellén Sanchén (Agrisost, 2019)
Context: Gender relations involve every human process. The creation of cooperatives in Cuba, especially in the municipality of Camagüey, is critical to dynamize the economy and promote productive techniques in the sector; the participation of men and women in this process is highly significant.